Activation of Substituted Metallocene Catalysts Using Methylaluminoxane. Issue 7 (10th February 2022) - Collins, Scott; Linnolahti, Mikko
Abstract: Activation of the metallocene complexes ( n ‐C4 H9 ‐(η 5 ‐C5 H4 ))2 ZrCl2 (BuCp2 ZrCl2 ) and rac ‐1, 2‐ethylenebis(1‐η 5 ‐C9 H6 )ZrCl2 (EBIZrCl2 ) using methylaluminoxane (MAO) was investigated by electrospray ionization mass spectrometry (ESI‐MS). Formation of dinuclear complexes at low Al : Zr ratios, which is accompanied by catalyst deactivation, occurs in the former case. In contrast, this behavior was not observed at similar Al : Zr ratios in the case of the EBIZrCl2 complex. Both active [BuCp2 ZrMe2 AlMe2 ][MAO(Me)] 3 and deactivated [(BuCp2 Zr)2 (μ‐CH2 )μ‐Cl][MAO(Me)] 9 complexes were detected in leaching experiments using a SiO2 ‐MAO‐supported BuCp2 ZrCl2 catalyst and excess MAO. DFT studies of the structure and UV‐Vis spectra calculated for the dinuclear cations 9 detected by ESI‐MS suggest that these species may account for long‐wavelength absorption seen in experimental spectra of complexes like BuCp2 ZrCl2 upon activation with MAO. Abstract : Activation of RCp2 ZrCl2 with MAO or MAO‐SiO2 at low Al : Zr ratios generates persistent [(RCp2 ZrMe)2 μ‐Cl][Me(MAO)] complexes which form deactivated [(RCp2 Zr)2 (μ‐CH2 )μ‐Cl][Me(MAO)] complexes through C−H activation as revealed by ESI‐MS and TD DFT simulation of UV‐Vis spectra.